Evaluating student's ability to assess treatment claims: validating a German version of the Claim Evaluation Tools - Jana Hinneburg; Barbara Gasteiger-Klicpera; Jürgen Kasper; Julia Lühnen; Katharina Maitz; Thomas Martens; Anke Steckelberg (BMC, 2023)
Abstract Background The Claim Evaluation Tools measure the ability to assess claims about treatment effects. The aim of this study was to adapt the German item sets to the target group of secondary school students (aged 11 to 16 years, grade 6 to 10) and to validate them accordingly. The scale's reliability and validity using Rasch's probabilistic test theory should be determined. Methods We conducted a sequential mixed-method study comprising three stages: contextualisation and adaption of the items (stage 1), piloting of the item sets using qualitative interviews (stage 2) and a construct validation by testing the unidimensional Rasch scalability for each item set after data collection in one secondary school in Germany and two secondary schools in Austria. We explored summary and individual fit statistics and performed a distractor analysis (stage 3). Results Secondary school students (n = 6) and their teachers (n = 5) participated in qualitative interviews in Germany. The qualitative interviews identified the need for minor modifications (e.g. reducing thematic repetitions, changing the order of the items). The data of 598 German and Austrian secondary school students were included to test for Rasch scalability. Rasch analyses showed acceptable overall model fit. Distractor analyses suggested that model fit could be improved by simplifying the text in the scenarios, removing and editing response options of some items. Conclusion After the revision of some items, the questionnaires are suitable to evaluate secondary school students' ability to assess health claims. A future goal is to increase the pool of items being translated and tested.